OVERVIEW OF METHODS OF POSITIONING STRATEGIES FOR LEADING UNIVERSITIES IN THE INTERNATIONAL INFORMATION SPACE - Shcherbak, Iryna (Mountain School of Ukrainian Carpaty, 2020)
The article defines the concept of "positioning strategy" and discusses the specific development of methods for positioning strategies of leading universities in the international information space by scientists. Researchers determine the choice of parameters by which positioning is carried out, not paying attention to the number of parameters. But, according to the author, this is undoubtedly an important factor, without which methodologies somewhat reduce their value. Selecting more parameters indicators improves the quality of the study, although it requires more time and energy. Having analyzed the classifications examined in the article, the researcher identified several determinant attributes (quantitative and qualitative). It is these signs, in his opinion, that demonstrate the effectiveness of positioning strategies of leading universities in the international information space. In a scientific study, the author examined the development of techniques for positioning strategies of enterprises from the point of view of various scientists. It is advisable to use these developments for developing strategies for positioning leading universities in the international information space. Important methodological aspects are the analysis of the positioning system of a higher educational institution as an instrument of influence on various spheres of society (political, economic, social and cultural spheres of life, etc.). After analyzing the psychological, pedagogical and specialized literature, the author came to the conclusion that at the present stage of the development of countries, there are many methods to increase competitiveness, namely: the model of the Boston advisory group; model of M. Porter; McKinsey method; Shell / DPM model LOTS method; PIMS method situational analysis (SWOT analysis); expert assessment method; Hofer / Shendel model; the financial and economic method, the method of mapping strategic groups and others. The conducted study makes it possible to assert that the main directions of the strategy for positioning HEI in the IIS in the management process are aimed at helping: identification and representation of specific features of the institution / educational service / educational product; implementation of the mission, goals, directions; analysis of consumer assessment of educational services of the university and its competitors; determination of the current state of positioning of HEI and prospects for its development; maintaining and expanding the results achieved.